A novel lncRNA YIL163C enhances genomic stability and antifungal resistance via the DNA damage response in Saccharomyces cerevisiae - Wang, Xueting; Li, Xuemei; Li, Duoyun; Zhang, Yiying; Bai, Bing; Chai, Bao; Wen, Zewen (Frontiers in Microbiology, 2025)
IntroductionLong non-coding RNAs (lncRNAs) are increasingly recognized as key regulators in cellular processes, including the DNA damage response (DDR). In Saccharomyces cerevisiae, DDR is critical for maintaining genomic integrity under stress, mediated by proteins like Mec1 and Rad53. However, the involvement of lncRNAs in DDR pathways, remains largely unexplored. This study investigates the function of a novel lncRNA, YIL163C, in promoting cell survival and genomic stability under DNA damage conditions.MethodsGenetic suppressor screening was employed to assess the role of YIL163C in rescuing lethality in mec1Δ sml1Δ and rad53Δ sml1Δ exposed to DNA damage. Proteomic and phosphoproteomic analyses were conducted to evaluate changes in protein abundance and phosphorylation states. The impact of YIL163C on DDR and antifungal drug tolerance, specifically to 5-fluorocytosine, was also examined.ResultsOverexpression of YIL163C was found to rescue lethality in mec1Δ sml1Δ and rad53Δ sml1Δ under DNA damage conditions. Proteomic analyses revealed that YIL163C modulates pathways related to DNA replication, ER stress response, and ribosome biogenesis, enhancing cellular resilience to HU-induced stress. Additionally, YIL163C reduced sensitivity to 5-fluorocytosine, indicating a role in antifungal drug tolerance. Phosphoproteomic data suggested YIL163C influences phosphorylation states, potentially acting downstream of the Mec1-Rad53 signaling pathway.ConclusionThis study provides new insights into the regulatory mechanisms of lncRNAs in DDR, with broader implications for antifungal therapy and genomic stability research, emphasizing the role of lncRNAs in stress responses beyond traditional protein-centric mechanisms.